1979
DOI: 10.1007/bf03350417
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure after pinealectomy in the rat

Abstract: Previous observations have suggested a role for the pineal gland in regulation of blood pressure. To investigate this possibility, pinealectomy was performed in prepubertal (43-day-old) and postpubertal (55-day-old) male rats. Systolic blood pressure (BP) was measured by the tail cuff method in conscious pinealectomized (Px) and sham pinealectomized (ShPx) rats at various times. In the 3 weeks following surgery, the BP increase after Px was twice that after ShPx (p less than 0.05). During administration of 1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…However, the arterial blood pressure and cerebral blood flow were not monitored in these pioneering studies. Although the antioxidant property of melatonin might account for its neuroprotective effect, monitoring cerebral blood flow is indispensable in pinealectomized rats because they may be hypertensive for the first 60 days after pinealectomy (Zanoboni et al, 1978; Vaughan et al, 1979) and also because melatonin has been reported to have a regulatory action on cerebral blood flow (Viswanathan et al, 1990, 1997; Mahle et al, 1997; Geary et al, 1997). We used rats that were pinealectomized 3 months before MCA occlusion to eliminate any possible action of pinealectomy-induced hypertension on stroke outcome (Zanoboni et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the arterial blood pressure and cerebral blood flow were not monitored in these pioneering studies. Although the antioxidant property of melatonin might account for its neuroprotective effect, monitoring cerebral blood flow is indispensable in pinealectomized rats because they may be hypertensive for the first 60 days after pinealectomy (Zanoboni et al, 1978; Vaughan et al, 1979) and also because melatonin has been reported to have a regulatory action on cerebral blood flow (Viswanathan et al, 1990, 1997; Mahle et al, 1997; Geary et al, 1997). We used rats that were pinealectomized 3 months before MCA occlusion to eliminate any possible action of pinealectomy-induced hypertension on stroke outcome (Zanoboni et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Pinealectomy leads to an increase in systemic arterial blood pressure (Karppanen et al, 1975; Zanoboni et al, 1978; Vaughan et al, 1979) in addition to a drastic reduction in circulating levels of melatonin (Ozaki and Lynch 1976; Lewy et al, 1980; Bubenik and Brown, 1997). Cerebral vessels express melatonin receptors (Viswanathan et al, 1990, 1997), and in vitro , melatonin has been shown to induce concentration-dependent vasoconstriction or dilation (Geary et al, 1997; Mahle et al, 1997).…”
mentioning
confidence: 99%
“…Brain protection is independent of hemodynamic changes and involves inhibition of caspase-3. arterial blood pressure [19][20][21] and either constricts or dilates blood vessels in a concentration-dependent manner [22,23]. In transient focal ischemia, it was previously shown in rats that melatonin increases cerebral laser Doppler flow (LDF) after tissue reperfusion [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its free radical scavenging actions, melatonin also exhibits pronounced vascular effects. Thus, melatonin reduces arterial blood pressure [10–13] and, depending on the dose and experimental condition, either constricts or dilates blood vessels [14, 15]. In the brain, melatonin increases cerebral blood flow (CBF) after focal ischemia [2] and also decreases the lower threshold of CBF autoregulation [16], suggesting stabilization of vascular function.…”
Section: Introductionmentioning
confidence: 99%